"You've got to keep moving, keep going": Understanding older patients' experiences and perceptions of delirium and nonpharmacological delirium prevention strategies in the acute hospital setting. Issue 13 (13th April 2020) - Lee‐Steere, Karen; Liddle, Jacki; Mudge, Alison; Bennett, Sally; McRae, Prue; Barrimore, Sally E.
Abstract: Aims and objectives: To explore older inpatients' experiences and perceptions of delirium and nonpharmacological delirium prevention strategies (NDPS). Background: Delirium is a distressing and serious complication in hospitalised older adults. NDPS (supporting nutrition, mobility and cognitive participation) have strong supporting evidence. Few studies have explored older inpatients' perspectives of these strategies. This information may assist staff to better support patient participation in NDPS. Design: Qualitative study using an interpretive descriptive (ID) methodological approach to explore older patient's experience of delirium and NDPS. Methods: Structured interviews of inpatients aged over 65 years across 6 medical and surgical wards explored patients' experiences and perceptions of delirium and prevention activities related to nutrition, mobility and cognition; and barriers and enablers to participation. Reporting used COREQ. Results: Twenty‐three participants were included (12 male, 11 reported delirium experience). Participants reported a range of physiological, emotional and psychological responses to delirium, hearing about delirium was different to experiencing it. Most participants were aware of the benefits of maintaining nutrition and hydration, physical activity and cognitive engagement in hospital. Barriers included poor symptom control, inflexible routines and inconsistent communication, whilst enablers included access to equipment, family involvement, staff encouragement and individual goals. These were organised into themes: outlook, feeling well enough, hospital environment, feeling informed and listened to, and support networks. Conclusion: A more patient‐centred approach to delirium prevention requires consideration of older people's values, needs, preferences and fit within the hospital environment and routines. Feeling informed, listened to and receiving support from staff and family carers can improve older inpatients' engagement in NPDS to prevent delirium in hospital. Relevance to clinical practice: Nurses are ideally placed to improve patient participation in NDPS through holistic assessment and care, addressing symptoms, providing clear information about delirium and delirium prevention, and facilitating family carer support and patient interactions.